2015
DOI: 10.1073/pnas.1514191112
|View full text |Cite
|
Sign up to set email alerts
|

Murine germinal center B cells require functional Fms-like tyrosine kinase 3 signaling for IgG1 class-switch recombination

Abstract: Switched antibody classes are important for efficient immune responses. Aberrant antibody production to otherwise harmless antigens may result in autoimmunity. The protein kinase fms-like tyrosine kinase 3 receptor (Flt3) has an important role during early B-cell development, but the role of Flt3 in peripheral B cells has not been assessed before. Herein we describe a previously unappreciated role for Flt3 in IgG1 class-switch recombination (CSR) and production. We show that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…On the other hand, Flt3 is also expressed in some lymphoid progenitors. Although its function in this ontogeny branch has not been explored as profoundly, it plays a role in the early differentiation of B cells [21] and is re-expressed by B cells in the germinal center [22]. Moreover, new data indicate that the Flt3L/Flt3 axis is necessary for the development of NK and type 2 and 3 innate lymphoid cells [23] and their progenitors [24].…”
Section: Expression Pattern Of Flt3 and Flt3lmentioning
confidence: 99%
“…On the other hand, Flt3 is also expressed in some lymphoid progenitors. Although its function in this ontogeny branch has not been explored as profoundly, it plays a role in the early differentiation of B cells [21] and is re-expressed by B cells in the germinal center [22]. Moreover, new data indicate that the Flt3L/Flt3 axis is necessary for the development of NK and type 2 and 3 innate lymphoid cells [23] and their progenitors [24].…”
Section: Expression Pattern Of Flt3 and Flt3lmentioning
confidence: 99%
“…Even though the intracellular response to FL might be different for different lymphoid lineages, this common pattern of Flt3 downregulation upon commitment and maturation to functional lymphocytes seems to indicate that active Flt3 signaling possibly contributes to the maintenance of an “immature” lymphoid phenotype and therefore it needs to be silenced in order for mature lymphoid cells to become functional. There have been reports of Flt3 re-expression on mature, activated B cells [ 101 , 102 ] and activated human T cells [ 103 ]. For B cells, this could be the result of Pax5 downregulation, which is necessary for further differentiation to antibody secreting plasma cells.…”
Section: The Role Of Fl In Normal Hematopoiesismentioning
confidence: 99%
“…For B cells, this could be the result of Pax5 downregulation, which is necessary for further differentiation to antibody secreting plasma cells. Some evidence for a potential functional significance of Flt3 expression on activated lymphocytes has been reported [ 102 ] but further investigations are required to elucidate the exact role of FL in this context.…”
Section: The Role Of Fl In Normal Hematopoiesismentioning
confidence: 99%
“…We found that CD11b was highly expressed to some extent after LPS stimulation, but there was no such change after anti-BCR stimulation (data not shown). TLRs on the surface of B cells are involved in the differentiation process of B cells in GC and induce the expression of AID, and it has been reported that LPS mediates long-term primary class-switched antibody responses and memory-like antibody responses in vivo ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%